Analysis Method of Black Liquor Pyrolysis and Gasification Using Deconvolution Technique to Obtain the Real Time Gas Production Profile - Joko Wintoko; Suryo Purwono; Mohammad Fahrurrozi; Bambang Soehendro (Jurnal Rekayasa Proses, 2020)
In thermal reaction experiments, e.g., pyrolysis, combustion, and gasification, the gas released from the reaction can be analyzed in gas measuring instruments. There will be some time delay due to the relatively long gas travel from the reactor to the analyzers. Besides, there can be some time lag in the gas measuring instrument. Gas dispersion may furthermore occur and thus alter the gas concentration profile. The observed gas concentration, therefore, can be very different from the original gaseous reaction products profile. A mathematical procedure called deconvolution technique will be used to get the original gaseous reaction products concentrations profile. The deconvolution technique is based on the assumption that original data have been altered by a transfer function to yield observed data. By the deconvolution techniques, the transfer function for each data set will be calculated and then can be used to compute the original data. In this study, the deconvolution technique was applied to the concentration profile of gaseous products from black liquor pyrolysis and gasification reactions measured by gas analyzers instruments to obtain the real-time gas concentration profile during the processes. Tracer gases are injected in the reactor To facilitate the deconvolution calculation, and their concentration profiles observed in the measuring instruments are recorded. Gaseous products that are analyzed are CO2, CO, CH4, SO2, and H2S. This technique can successfully provide the real-time gas production concentration profile from the black liquor pyrolysis and gasification reaction. A B S T R A KDalam reaksi termal seperti pirolisis, pembakaran, dan gasifikasi, gas hasil reaksi dapat dianalisis dengan instrumen analisis gas. Akan ada penundaan waktu deteksi karena waktu tempuh dari reaktor ke alat analisis. Ada juga tambahan waktu karena pemrosesan dalam instrumennya. Dispersi gas juga mungkin terjadi yang akan mengubah profil konsentrasi gas.Profil konsentrasi gas yang terdeteksi bisa jadi akan sangat berbeda dengan profil produksi gas yang sebenarnya. Untuk mendapatkan profil konsentrasi yang sebenarnya, dapat digunakan sebuah prosedur matematika yang disebut dekonvolusi. Dalam prosedur ini diasumsikan profil gas telah diubah oleh sebuaf fungsi transfer sehingga menghasilkan profil gas terboservasi. Dengan teknik dekonvolusi, fungsi transfer ini akan dicari sehingga bisa dipergunakan untuk menghitung profil gas sebenarnya.  Dalam penelitian ini profil gas hasil reaksi pirolisis dan gasifikasi lindi hitam yang terdeteksi dalam instrumen analisis gas akan didekonvolusi untuk mendapatkan profil produksi gas yang sebenarnya. Untuk itu sebuah gas pendeteksi diijeksikan ke dalam reaktor dan profil konsentrasinya diukur dengan instrumen analisis. Gas yang dianalisis adalah CO2, CO, CH4, SO2, and H2S. Dengan teknik ini profil produksi gas yang sebenarnya dari reaksi pirolisis dan gasifikasi berhasil diperoleh.